Berimbau: instances of shared decisionmaking in collaborative composition (Orfeu, 2020)
This article offers reflections about the collaborative process in creation of Berimbau for piano, voice and electroacoustic sounds. The intended objectives were: a) to offer a wide panorama of perspectives on the state of the art in research on artistic collaboration (JOHN-STEINER, 2000; BARRET, 2014) and of distributed creativity (CLARKE; DOFFMAN, 2017); b) to briefly describe the composition theories developed by Laske (1991) and Reynolds (2002), illuminated by Rios Filho (2010); and c) from those, reflect upon instances of shared decision-making between collaborators in the composition process of the work Berimbau. In order to do so, we refer to specific episodes from our collaboration process to exemplify the various phases and instances of decisions. We believe that the approach presented here complements other research in this area, contributing to deeper understanding of artistic collaboration.
Keywords: Collaborative composition; shared decision-making; composer-performer collaboration